The Difference Between Covid-19 Virus and Influenza - Noor S. Naji; Sura I.A.Jabuk; Rasha Kadhim Mahdi; Raflaa S.Hussien; Zahraa M. Altaee (Scholars Digest Publishing, 2023)
Viruses in the Covid-19 family, which are widespread in both people and animals, typically cause mild-to-moderate respiratory infections. Animals in an open-air market are thought to be the source of COVID-19, which may be a newly discovered bat coronavirus. The flu is a contagious respiratory infection that often affects the nose, throat, and lungs but can also spread quickly. Influenza viruses are the cause. There is a great similarity between the influenza virus and the emerging coronavirus, but in contrast, there are some differences that help distinguish between, their effect on the respiratory system, as they are transmitted in the same ways, whether through direct contact with an infected person or touching a surface carrying the virus, but different in symptoms Initial, incubation period, treatment, complications, and vaccine availability.
Keywords: Coronavirus, Infection, Incubation Period, influenza.